Breaking Down BBC News Headlines: A Study of Structure Types - Dewi, Ni Made Ratna; Devi Maharani, Putu (Humanis; Vol 27 No 4 (2023)DO - 10.24843/JH.2023.v27.i04.p08, 2023)
This study aims to find the structure types used in BBC News headlines. This research used Morley's (2000) theory for sentence types and Matthews' (1981) theory for phrase types as well as Brown & Miller's (1991) theory to analyze its constituent structure. This research used descriptive qualitative method to explain the final result of the research. The data sources were obtained from 186 BBC headlines for the period July 2023 which were then presented in a table according to the frequency of occurrence. The results showed that based on the sentence types, there are three sentence types found, namely simple sentences, complex sentences, and compound sentences. Among the sentence types used, simple sentences are the most frequent, with 151 occurrences, followed by complex sentences with 20 occurrences, and compound sentences with three occurrences. Furthermore, based on the phrase types, 11 headlines with noun phrase structure and one headline with verb phrase structure were found. It is hoped that after this research is conducted, it can make a positive contribution to the development of science, especially in the field of syntax.